Evaluasi Kondisi Geologi Teknik dalam Pembangunan Embung - I Gde Budi Indrawan; Shinta Dwi Novianti; Heru Hendrayana; Doni Prakasa Eka Putra; Wahyu Wilopo (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
Pucang Village was consisted of eruption materials of Merapi Volcano. The relatively high coefficient of permeability of the materials consisting this area caused rainwater to directly infiltrate into the ground. Evaluation of engineering geological conditions was conducted for construction of a detention pond in this area, which had limited water supply for daily activities. The evaluation was conducted on results of a 1:10.000 scale of engineering geological mapping and analyses of 1:10.000 scale of geological disaster maps produced by previous researchers. The engineering geological mapping involved mapping of morphological condition and active geomorphic process, lithological condition, existence of geological structure, and water source location. The evaluation results showed that the proposed location met the land suitability criteria for detention pond construction based on the morphological condition and active geomorphic process, existence of geological structure, and water source location, but did not meet those based on the lithological and vulnerability to Merapi Volcano eruption disaster. Construction of impermeable layer to prevent water seepage into the ground and periodic removal of sediment in the base of the detention pond were suggested to be carried out to keep the detention pond functioning properly.